Esketamine versus fentanyl as adjuncts to hepatic hilar nerve block for ambulatory percutaneous liver tumor ablation focusing on respiratory safety: protocol for a randomized controlled trial - Wang, Xiao; Yan, Lijuan; Cai, Jiaying; Wei, Jianfei; Zhang, Zuobing; Yang, Bin (Frontiers in Pharmacology, 2025)
BackgroundOpioid-induced respiratory depression (OIRD) is a critical safety concern during ambulatory percutaneous liver tumor thermal ablation. Esketamine has been shown to offer a promising opioid-sparing alternative with the potential to provide respiratory stability benefits. We hypothesize that hepatic hilar nerve block (HHNB) combined with esketamine will reduce the incidence of respiratory depression when compared to HHNB in conjunction with fentanyl in this particular context.MethodsThis single-center, prospective, double-blind, randomized controlled trial (RCT) will enroll patients undergoing ambulatory ultrasound-guided percutaneous liver thermal ablation. Patients will be randomly assigned to receive either intravenous esketamine 0.37 mg kg−1 (Intervention group) or intravenous fentanyl 1 μg·kg− (Control group). All subjects will receive a standardized premedication consisting of midazolam 0.03 mg kg−1 IV, followed by ultrasound-guided HHNB.Results and analysisThe primary outcome is the incidence of respiratory depression, defined as SpO2 <90% or EtCO2 >55 mmHg. Secondary outcomes include the rate of anesthesia success, postoperative pain scores, and the consumption of remedial analgesia at 2, 6, and 24 h post-surgery. Additionally, satisfaction scores from both the sonographer and the patient are considered, along with any adverse events that may occur. The statistical analysis will utilize appropriate parametric/non-parametric tests for continuous data and chi-square/Fisher’s exact tests for categorical data (significance p < 0.05), using SPSS (v20.0) and R (v4.4.3; R Foundation) within the RStudio environment (v2024.12.1 + 563).Conclusion and discussionThis trial aims to provide Level I evidence comparing the respiratory depression risk between esketamine-based and fentanyl-based analgesia during HHNB-guided liver ablation. Should esketamine prove to be demonstrably superior in terms of respiratory safety, HHNB-esketamine has the potential to be a viable treatment option.